“Understanding the words of relationships”: Language as an essential tool to manage CSR in communities of place - Selmier II, W Travis; Newenham-Kahindi, Aloysius; Oh, Chang Hoon (Journal of International Business Studies, 2015)
Multinational enterprises (MNEs) encounter relentless stakeholder pressures when operating across linguistic, cultural and institutional boundaries. Our aims are to examine whether and how acquisition of language resources may help MNEs to bridge these boundaries and reduce pressures on MNE legitimacy by improving their corporate social responsibility (CSR) outcomes. We propose an MNE model of language resource acquisition policy based on three language orientations: “language-as-problem,” “language-as-resource” and “language-as-right.” Using sociolinguistic tools – an “ecological” analysis of how language affects MNE–stakeholder relationships – and surveying 15 mining MNEs from Australia, Canada, China, South Africa, Switzerland and the United Kingdom operating in East Africa, our research found some MNEs employ regional lingua francas like Swahili and local leadership practices to build sustainable relationships with local stakeholders. These local stakeholders are members of communities of place (CofP), who steward the land their ancestors have inhabited for centuries, and their voices have grown as to how that land is used. As their voices have grown, MNEs should improve CSR outcomes with CofP through better communications. A well-designed language acquisition policy may improve such communication and so fend off threats to MNE legitimacy.